The effect of a career development programme based on the Hope-Action Theory: Hope to Work for refugees in British Columbia. Issue 1 (2nd January 2019) - Yoon, Hyung Joon; Bailey, Natasha; Amundson, Norman; Niles, Spencer
ABSTRACT: The purpose of this study was to assess the proximal and distal outcomes of a career development training programme for refugees that was developed based on the Hope-Action Theory (HAT). Adopting an experimental design, proximal outcomes such as self-efficacy, hope-action competencies, job search clarity, and career adaptability were assessed three times; and distal outcomes including employment status, job-seeking activities, career growth, hopeful career state, work engagement, and job satisfaction were assessed once at nine months. We used a two-way mixed effects analysis of covariance and a serial mediation analysis. The programme was effective in developing hope-action competencies, general self-efficacy, and job search clarity. The experimental group participants exhibited higher hopeful career state and work engagement. A serial mediation model of the HAT-based intervention predicting job satisfaction was found. Limitations and future directions are discussed.